2014
DOI: 10.3892/or.2014.3354
|View full text |Cite
|
Sign up to set email alerts
|

USP22 promotes epithelial-mesenchymal transition via the FAK pathway in pancreatic cancer cells

Abstract: Epithelial-mesenchymal transition (EMT) contributes to the occurrence and development of tumors, particularly to the promotion of tumor invasion and metastasis. As a newly discovered ubiquitin hydrolase family member, USP22 plays a key role in the malignant transformation of tumors and the regulation of the cell cycle. However, recent studies on USP22 have primarily focused on its role in cell cycle regulation, and the potential mechanism underlying the promotion of tumor invasion and metastasis by abnormal US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…Our results also demonstrated that USP22 can increase cell migration and invasion abilities via EMT induction. According to the results of previous studies, USP22 can induce EMT by regulating TGF-β1 in lung cancer cells [8], and elevated USP22 expression can promote EMT by up-regulating ZEB1 and Snail in pancreatic cancer cells though a process that involves focal adhesion kinase (FAK) signaling [29]. The present study has revealled an additional novel mechanism by which USP22 induces EMT.…”
Section: Discussionsupporting
confidence: 60%
“…Our results also demonstrated that USP22 can increase cell migration and invasion abilities via EMT induction. According to the results of previous studies, USP22 can induce EMT by regulating TGF-β1 in lung cancer cells [8], and elevated USP22 expression can promote EMT by up-regulating ZEB1 and Snail in pancreatic cancer cells though a process that involves focal adhesion kinase (FAK) signaling [29]. The present study has revealled an additional novel mechanism by which USP22 induces EMT.…”
Section: Discussionsupporting
confidence: 60%
“…Phosphorylation and dephosphorylation of Ezrin at T567 has been identified as a critical step in the conformational activation and deactivation of Ezrin [44]. Our previous studies confirmed that phosphorylated Ezrin could mediate EMT in pancreatic cancer cells through the FAK pathway and promote invasion and metastasis [45]. In this study, during the EMT induced by TCM, Ezrin phosphorylation (T567) increased significantly (Figure 4A), which is similar to the expression of FUT4/LeY (Figure 2B).…”
Section: Discussionmentioning
confidence: 83%
“…[47][48][49] Activation of the SRC tyrosine kinase facilitates EMT through the FAK and phosphatidyl inositol-3 kinase signaling pathways. 50 Our present results suggest that AJAP1 mediated the EMT of HCC cells through regulation of SRC transcription and its related signaling pathways. Further investigation of the correlation between the expression of AJAP1 and EMT-associated molecules is required to understand HCC pathogenesis.…”
Section: Discussionmentioning
confidence: 83%